MiR 221/222 as New Players in Tamoxifen Resistance - Sadat Alamolhodaei, Nafiseh; Behravan, Javad; Mosaffa, Fatemeh; Karimi, Gholamreza (Current Pharmaceutical Design, 2016)
Breast cancer is the most frequent cancer in women. Despite advances in early detection and treatment, it has the second highest mortality rate after lung cancer. Around 85% of breast carcinomas are ER+; thus, antiestrogens like tamoxifen are beneficial. Although, tamoxifen is useful for many patients, a number of patients respond poorly to initial therapy or recurrence occurs in about 30% of cases, because tamoxifen resistance happens. Drug resistance remains a major clinical obstacle to successful treatment of breast cancer and more than 90% of unsuccessful treatments are because of acquired resistance and MultiDrug Resistance (MDR) is a major contributor. MicroRNAs are members of a novel class of short noncoding RNAs. Besides their various roles in gene expression, miRNAs are considered as important cancer therapeutic targets and biomarkers. Since 2005, when miRNA deregulation was first reported in breast cancer, more than 1000 reports have been published about miRNAs. Increasing number of studies showed the importance of miRNAs in antiestrogen therapy, especially on tamoxifen; thus, it is not surprising that these tiny molecules are involved in drug resistance. Due to the pivotal role of these known RNA molecules, in this review, we tried to illustrate the importance of the miRNAs as a new player in breast cancer pathogenesis. We have also focused on cancer drug resistance mechanisms highlighting the role of important oncomirs, miR 221/222, involved in cell cycle deregulation in breast cancer. The relationship between these oncomiRs with resistance to tamoxifen is also emphasized.
Keywords: Tamoxifen resistance